1989
DOI: 10.1007/bf00266715
|View full text |Cite
|
Sign up to set email alerts
|

Homologous meniscus transplantation

Abstract: The increase in severe ligament injuries of the knee has led to consideration of the need for meniscal transplantation in reconstructive operations for chronic rotational instability. Transplantation of the medial meniscus was carried out in two groups of 15 sheep. In one group lyophilised, gamma-sterilised allogenic menisci were transplanted and these underwent a complete remodelling in 48 weeks. In the other group, deep frozen allogenic menisci were used and these remained fully functional without remodellin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
104
1
6

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 406 publications
(113 citation statements)
references
References 21 publications
2
104
1
6
Order By: Relevance
“…Other researchers have studied the effects of meniscal transplantation. Milachowski et al [32] were the first to report their results with meniscal allograft transplantation in 1989. They performed medial meniscal transplantation in 22 knees and demonstrated that meniscal transplantation was a viable option but raised concerns over the use of freeze dried grafts (lyophilized) and graft shrinkage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other researchers have studied the effects of meniscal transplantation. Milachowski et al [32] were the first to report their results with meniscal allograft transplantation in 1989. They performed medial meniscal transplantation in 22 knees and demonstrated that meniscal transplantation was a viable option but raised concerns over the use of freeze dried grafts (lyophilized) and graft shrinkage.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous animal and human studies have shown that transplanted menisci do heal, especially at the peripheral rim [5,6,15,21,32,49,50,51]. Correct sizing of the meniscal allograft is critical for healing.…”
Section: Indications For Meniscal Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…Milachowski from Munich, Germany, performed the first meniscus allograft transplantation in 1984 using lyophilisation as preservation method 4. Despite the observed shrinkage of the grafts, this study provided proof of principle that meniscus transplantation results in a remarkable clinical benefit.…”
Section: Introductionmentioning
confidence: 86%
“…An transplant alleviates pain and improves function as well as having a satisfactory survival rate [10,11]. Drawbacks of these allografts are limited availability, size mismatching, high costs, graft shrinkage after implantation and risk of transmission of disease [12,13]. Alternatively, there are several biodegradable implants based on synthetic and natural polymers available but these implants demonstrate other disadvantages such as lack of durability in loading conditions [14][15][16].…”
Section: Introductionmentioning
confidence: 99%